O PROTAGONISMO SURDO: A REPRESENTAÇÃO DA SURDEZ EM CRISÁLIDA - MATTOS, ALAN MARLON DE (2023)
This research reflects on the deaf protagonism and the representation of deafness in a media narrative, aiming to understand how the deaf culture has been highlighted by the media. The concepts of identity, alterity and representation are problematized, starting from a perspective amonging the Cultural Studies and Deaf Studies. The Deaf Studies are an extension of Cultural Studies, that discuss crucial concepts for understanding the deaf community, for example, the Deafhood, a key concept in Deaf Studies that adresses the power dynamics between the deaf individuals and hearing individuals, presenting the deaf way of being an experience the world. To discuss these concepts and achieve the proposed objectives, the research focuses on the series Crisálida, the first bilingual Brazilian Sign Language (Libras)- Portuguese series produced in Brazil that brings Sign Language in the foreground. Therefore, for the development of this research, the guiding question is: how does Crisálida (2020) problematizes the representation of deafness and the construction of deaf identities?To comprehend the proposed objectives and adress the research question, a methodological approach is outline based on the analysis of serialized narrative. Through the analysis of Crisálida, it is concluded that the series shows the deaf culture and the different experiences of this community, countering hearing-centric and stereotypical discourses about deafness. Additionally, the relevance and social impact that the series has, in a way to demystiy misconceptions about deaf culture and contributing to the dissemination of Sign Language and deafness from a cultural perspective.